A meta-analysis of prognostic value of KIT mutation status in gastrointestinal stromal tumors - Jiang, Zhiqiang (Onco Targets Ther, 2016)
Numerous types of KIT mutations have been reported in gastrointestinal stromal tumors (GISTs); however, controversy still exists regarding their clinicopathological significance. In this study, we reviewed the publicly available literature to assess the data by a meta-analysis to characterize KIT mutations and different types of KIT mutations in prognostic prediction in patients with GISTs. Twenty-eight studies that included 4,449 patients were identified and analyzed. We found that KIT mutation status was closely correlated with size of tumors and different mitosis indexes, but not with tumor location. KIT mutation was also observed to be significantly correlated with tumor recurrence, metastasis, as well as the overall survival of patients. Interestingly, there was higher risk of progression in KIT exon 9-mutated patients than in exon 11-mutated patients. Five-year relapse-free survival (RFS) rate was significantly higher in KIT exon 11-deleted patients than in those with other types of KIT exon 11 mutations. In addition, RFS for 5 years was significantly worse in patients bearing KIT codon 557–558 deletions than in those bearing other KIT exon 11 deletions. Our results strongly support the hypothesis that KIT mutation status is another evaluable factor for prognosis prediction in GISTs.